Theorizing on entrepreneurial orientation in international business: A synthetic review - Vijay Narayanan (International Entrepreneurship Review, 2017)
Both, entrepreneurship and international business have been topics of interest for academicians, businessmen and policy-makers around the world. Now it is obvious that entrepreneurs also do business internationally. International entrepreneurship is still a new research domain within international business studies and current empirical investigations focus on entrepreneurial orientation while internationalizing. The main objective of the paper is to discuss the concept of the international entrepreneurial orientation, by linking entrepreneurial orientation and internationalisation of the firm. The article is based on in-depth literature review and its critics.